The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/adsc.201400417
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal‐Free Direct Trifluoromethylation of 2,3‐Dihydropyridin‐4(1H)‐ones at Room Temperature

Abstract: A transition metal‐free, regioselective C‐5 trifluoromethylation of 2,3‐dihydropyridin‐4(1H)‐ones (cyclic enaminones) with trimethyl(trifluoromethyl)silane (TMSCF3) was developed that proceeds under mild conditions at room temperature. This direct transformation was successful with both electron‐rich and electron‐deficient cyclic enaminones. This method bypasses substrate prefunctionalization and transition metal catalysis, and allows the convenient and direct access to a variety of medicinally important 3‐tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Accordingly, their syntheses have attracted tremendous attention from synthetic chemists . In recent years, our group and other groups have developed efficient methods for the construction of functionalized enamides via direct sp 2 C–H bond functionalization of simple enamides. Enaminones are another class of enamine derivative that have attracted the attention of synthetic chemists since they contain additional functional groups that can be easily manipulated .…”
mentioning
confidence: 99%
“…Accordingly, their syntheses have attracted tremendous attention from synthetic chemists . In recent years, our group and other groups have developed efficient methods for the construction of functionalized enamides via direct sp 2 C–H bond functionalization of simple enamides. Enaminones are another class of enamine derivative that have attracted the attention of synthetic chemists since they contain additional functional groups that can be easily manipulated .…”
mentioning
confidence: 99%
“…Dihydropyridones bearing the CF 3 group have attracted attention as intermediates for the preparation of biologically important CF 3 -piperidines . But the range of such dihydropyridones as well as approaches to their synthesis is limited by the small number of protocols including radical trifluoromethylation . It should be noted that 6-CF 3 -2,3-dihydro-4-pyridones are hard-to-reach compounds, and in the literature, the only example of them, ethyl 6-(4-chloro­phenyl)-4-oxo-2-(trifluoro­methyl)-1,4,5,6-tetrahydro­pyridine-3-carboxylate, has been described .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The rst and only study on metal-free direct triuoromethylation of cyclic alkenes was reported by Georg and co-workers in 2014. 36 It described the regioselective introduction of a CF 3 group at the C-5 position of 2,3-dihydropyridin-4(1H)-ones (cyclic enaminones) using PhI(OAc) 2 as an oxidant and the Ruppert's reagent. A screening of reaction conditions proved that KF and MeCN were the most effective base and solvent, respectively.…”
Section: Internal Alkenesmentioning
confidence: 99%